Do family firms engage in less tax avoidance than non-family firms? The corporate opacity perspective. Issue 2 (August 2021) - Lee, Cheng-Hsun; Bose, Sudipta
Highlights: Family firms engage in less tax avoidance than non-family firms, ceteris paribus . Corporate opacity attenuates the negative association between family firms and tax avoidance. Tax avoidance by and corporate opacity of family firms are negatively associated with firm valuation. Corporate opacity perspective needs to consider to gain a better understanding of the dominant shareholder–minority shareholder agency conflict as it relates to tax avoidance. Abstract: We examine the moderating effect of corporate opacity on the relationship between family firms and tax avoidance. We find, ceteris paribus, that family firms and tax avoidance are negatively associated. However, the negative association is attenuated when corporate opacity increases. Our results indicate that corporate opacity affects firms' tax avoidance, with this effect stronger for family firms than for non-family firms. We also find that tax avoidance by and corporate opacity of family firms are negatively associated with firm valuation. These results are consistent with the opportunistic perspective that family firms engage in more tax avoidance than non-family firms when corporate opacity is higher.